Retained Morbidly Adherent Placenta Presenting as a Myometrial Mass in Patients With Vaginal Bleeding: A Case Series and Review of Current Literature. Issue 4 (14th December 2022) - Noblett, Dylan; Sekhon, Simran; Corwin, Michael T.; Lamba, Ramit; McGahan, John P.
Abstract: The differential diagnosis for a uterine mass and vaginal bleeding after abortion or delivery is broad and includes both benign and malignant causes. A rare etiology for this condition is retained morbidly adherent placenta. Few cases of retained morbidly adherent placenta presenting as a myometrial mass in the setting of vaginal bleeding have been described in the medical literature. In this case series and review of the current literature, we describe the ultrasound features of 3 retained morbidly adherent placentae, along with correlative magnetic resonance imaging findings.